Effects of nutritional health consciousness on consumer's goat milk consumption - Lee-Chang L.; Rahman H.A.; Shamsir M.; Aris M.; Kok-Siew H.; Rani M.D.M.; Zairina A. Rahman (Serials Publications, 2024)
Indexed by Scopus